State of hepatobiliary system at endocrinous pathology - Ye. B. Kravets; M. A. Medvedev; I. A. Kolmatsuj; Ye. A. Birjulina (Бюллетень сибирской медицины, 2005)
The aim of research is to estimate clinicopathologic aspects of hepatobiliary system abnormalities at leading endocrinous diseases among children and adolescents.There were examined 140 children and adolescents with thyroid gland pathology and 125 children with diabetes mellitus of 1 type. Comparison group consists of 30 children. There was estimated hepatobiliary system condition using fractional duodenal intubation, bile biochemistry, US of liver and gall-bladder, dynamic radionuclide hepatobiliary imaging. It was determined that changes from side of hepatobiliary system depend mostly from functional characteristic of thyroid gland than from duration of disease at pathology of thyroid gland. Changes in biochemical composition of bile at thyreopathy were conditioned by abnormality of biliary excretion motor activity. Clinic-functional changes from hepatobiliary system occurred in 50% of cases and fatty hepatosis was mostly frequent diagnosed at SD of the 1st type. There were suggested complex of diagnostic examination in order to define pathology of hepatobiliary system at endocrinopathy.